The new strategic brand management : advanced insights and strate gic thinking - Kapferer, Jean-Noel. (London ; Philadelphia : Kogan Page, 2012)
"Adopted internationally by business schools, MBA programmes and mar keting practitioners alike, The New Strategic Brand Management is simpl y the reference source for senior strategists, positioning professional s and postgraduate students. Over the years it has not only established a reputation as one of the leading works on brand strategy but also ha s become synonymous with the topic itself. The new edition builds on th is impressive reputation and keeps the book at the forefront of strateg ic brand thinking. Revealing and explaining the latest techniques used by companies worldwide, author Jean-Noël Kapferer covers all the leadin g issues faced by the brand strategist today, supported by an array of international case studies. With both gravitas and intelligent insight, the book reveals new thinking on topics such as putting culture and co ntent into brands, the impact of private labels, the new dynamics of ta rgeting and the comeback of local brands"--
Includes bibliographical references (p. [469]-481) and index.
Keywords: Brand name products -- Management